Effectiveness of “Eat right, be positive about your body and live actively” programme in preventing overweight and disordered eating among Malaysian adolescents - Sharif Ishak, Sharifah Intan Zainun (2019)
Obesity and disordered eating (DE) have potential shared risk factors, including dietary practice, physical activity level and body image perception. Thus, prevention of both obesity and DE can be done simultaneously. The present study aimed to evaluate the effectiveness of the ‘Eat Right, Be Positive about Your Body and Live Actively’ (EPaL) intervention programme for preventing risk of becoming overweight and DE in Malaysian adolescents. The EPaL intervention programme promoted three main components of healthy lifestyle, namely healthy eating, positive body image and active lifestyle. The present study comprised two phases, in which Phase 1 of the study aimed to develop the EPaL intervention programme and Phase 2 of the study aimed to evaluate the effectiveness of the EPaL intervention programme. The Phase 1 of the study started with a needs assessment, and followed by the development of the EPaL Educational Package (EPaL Educational Module, EPaL Activity Book and EPaL Educational/ Activity Cards and Posters) for adolescents. The needs assessment was conducted using focus group discussions involved 72 secondary school adolescents in Form 1 and Form 2. The EPaL Educational Package, which consisted of EPaL Module: Volume 1 (Topic 1 until Topic 4) and EPaL Module: Volume 2 (Topic 5 until Topic 8), was developed. Content validity of the EPaL Educational Package by a team of expert panels was conducted. The face validity assessment of the EPaL intervention programme involved 54 adolescents aged 11-16 years who evaluated the EPaL intervention programme. The Phase 2 of the study was the evaluation of the effectiveness of the EPaL intervention programme among secondary school adolescents. This study used a quasi-experimental study design. Peer education was applied in coveying the knowledge and skills on healthy lifestyle to the adolescents. It compared the effects of the intervention on personal, eating and physical activity behaviour variables, and health outcomes, between intervention (IG) and comparison groups (CG). The comparisons were determined at three time points - before intervention (pre-intervention), after intervention (Post I) and 3 months after intervention (Post II). The IG received EPaL intervention programme for 16 weeks while CG received no intervention and had their standard Physical Education and Health classes. There were 76 adolescents (IG: n=34; CG: n=42) in Form 1 and Form 2 included in the final analysis.